Ruthenium-Catalyzed Directed C(3)–H Olefination of N-Acetyl-1,2-dihydroisoquinolines: A Method to Achieve C3-Olefinated Isoquinolines - Das, Riki; Khot, Nandkishor Prakash; Deshpande, Akanksha Santosh; Kapur, Manmohan (Synthesis, 2019)
A unique approach to achieve regioselective C(3)–H olefination of isoquinolines under ruthenium-catalyzed conditions has been developed. The acetyl group of N-acetyl-1,2-dihydroisoquinoline acts as a directing group for this C–H olefination strategy. Removal of the acetyl directing group by a simple method leads to a quick access to C-3 olefinated isoquinolines. The methodology is a very good alternative to the traditional Heck reaction and substrates with halogen substituents are very good candidates for the transformation.
Keywords: ruthenium catalysis; C–H functionalization; isoquinolines; directing group; C–H olefination